Prospek Pengaturan Cryptocurrency sebagai Mata Uang Virtual di Indonesia (Studi Perbandingan Hukum Jepang Dan Singapura) - Yudhi Priyo Amboro; Agustina Christi (Journal of Judicial Review, 2019)
The development of information technology requires humans in modern times to adjust. Various modern payment instruments have been designed so that they can be used as a means to facilitate transactions. In addition to e-money, in recent years a virtual currency has emerged, known as cryptocurrency. In this paper, researchers formulated the problem form, including: comparison of Japanese and Singapore cyrptocurrency laws, payment systems in Indonesia at this time and then compared the prospects for the development of cryptocurrency whether it can be implemented in Indonesia in facing the globalization of the world. This research was conducted using a normative research method which was then compared to written regulations, theories, journals obtained from library materials. The current legal conflict faced by the State is that virtual currencies are not allowed to transact in Indonesia by the government. So this research was conducted with the aim of analyzing comparative law studies related to the prospects for the development of cryptocurrency in Indonesia, as well as examining whether cryptocurrency arrangements could be made in Indonesia.